Practical game design : a modern and comprehensive guide to video game design - Kramarzewski, Adam; De Nucci, Ennio (Packt Publishing Ltd., 2023)
If you’re in search of a cutting-edge actionable guide to game design, your quest ends here! Immerse yourself in the fundamentals of game design with expert guidance from veterans with decades of game design experience across a variety of genres and platforms. The second edition of this book remains dedicated to its original goal of helping you master the fundamentals of game design in a practical manner with the addition of some of the latest trends in game design and a whole lot of fresh, real-world examples from games of the current generation. This update brings a new chapter on games as a service, explaining the evolving role of the game designer and diving deeper into the design of games that are meant to be played forever. From conceptualizing a game idea, you’ll gradually move on to devising a design plan and adapting solutions from existing games, exploring the craft of producing original game mechanics, and eliminating anticipated design risks through testing. You’ll then be introduced to level design, interactive storytelling, user experience and accessibility. By the end of this game design book, you’ll have learned how to wrap up a game ahead of its release date, work through the challenges of designing free-to-play games and games as a service, and significantly improve their quality through iteration, playtesting, and polishing.